2016
DOI: 10.1186/s12864-016-3162-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression in the midgut of Bombyx mori during the larval molting stage

Abstract: BackgroundInsects can be models for understanding human intestinal infection and pathology. Molting, a special period during which the old insect cuticle is shed and a new one is produced, is crucial for insect development. Holometabolous insects may experience several larva-to-larva moltings to become larger, a pupal molt and adult eclosion to become adults. During the larval molts, they stop feeding and become quiescent. Although the molting larvae become quiescent, it is not known if changes in microbiome, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 63 publications
(125 reference statements)
1
26
1
Order By: Relevance
“…The silkworm, B. mori , is a typical complete metamorphosis type insect and undergoes six molting stages, which are special periods of the life cycle. There are substantial variations in metabolic pathways and physiological and biochemical characteristics before and after each molting stage, including changes in gene expression, chitin synthesis, cuticle sclerotization and replacement, epidermal staining, midgut cells regeneration and apoptosis (Yang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The silkworm, B. mori , is a typical complete metamorphosis type insect and undergoes six molting stages, which are special periods of the life cycle. There are substantial variations in metabolic pathways and physiological and biochemical characteristics before and after each molting stage, including changes in gene expression, chitin synthesis, cuticle sclerotization and replacement, epidermal staining, midgut cells regeneration and apoptosis (Yang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that the expression of many genes undergoes regulatory changes in the epidermis during molting stages (Yang et al, 2016; J. Zhang, Lu, Kong, Zhang, & Ling, 2014). The gene BmC 1 ‐THF encodes a crucial enzyme in folate metabolism and is important for the synthesis of nucleic acids and proteins as well as DNA methylation and repair (Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The developmental and tissue expression patterns of the Tribolium SPCs were analyzed by RT‐PCR. Total RNA was isolated from whole insects at various stages by using the TRIZOL REAGENT (Invitrogen, Carlsbad, CA) (Yang et al., ). To assay gene expression in the midgut and carcass (whole body minus gut), 30 individuals were dissected to obtain separate pools of gut and carcass.…”
Section: Methodsmentioning
confidence: 99%